Transcriptome responses of RNAi-mediated ETH knockdown in Scylla paramamosain at different premolt substages - Chan, Siuming-Francis; Wen, Qi-Qiao; Ao, Chun-Mei; Wang, Wei; Wang, Cheng-Gui; Zhao, Yan-Fei (Frontiers in Endocrinology, 2022)
Ecdysis triggering hormone (ETH) plays an important role in molting, reproduction, and courtship behavior in insects. To investigate the potential downstream pathways and genes of ETH in Scylla paramamosain, RNA interference (RNAi) was conducted on crabs at early (D0) and late (D2) premolt substages, and the transcriptome profiles of each group were compared by RNA-sequencing. Real-time quantitative polymerase chain reaction (RT-qPCR) and semi-quantitative polymerase chain reaction (RT-PCR) result showed a significant knockdown of ETH at D0 stage, whereas a significant increase was shown conversely in crabs at D2 substage after the injection of dsETH. A total of 242979 transcripts were assembled, and 44012 unigenes were identified. Transcriptomic comparison between crabs at D2 and D0 substages showed 2683 differentially expressed genes (DEGs), these genes were enriched in ribosome and pathways related to transcription factor complex and cell part; 20 DEGs were identified between dsETH-injected and dsGFP-injected crabs at D0 substage, these DEGs involved in carbohydrate metabolism, One carbon pool by folate, and chitin binding; 26 DEGs were identified between dsETH-injected and dsGFP-injected crabs at D2 substage, these DEGs involved in calcium channel inhibitor activity, fat digestion and absorption, and cardiac muscle contraction. RT-qPCR verified the differential expression of selected genes. In conclusion, crabs at D0 substage are more active in preparing macromolecular complex that is needed for molting. Moreover, ETH has potential roles in carbohydrate metabolism, one carbon pool by folate and chitin binding for crabs at D0 substage, while the role of ETH turns to involve in calcium channel inhibitor activity, fat digestion and absorption, and cardiac muscle contraction at D2 substage, to facilitate the occurrence of molting. The selected DEGs provide valuable insight into the role of ETH in the regulation of crustacean molt.